Determinants of Corporate Value (Empirical Studies of Manufacturing Sector 2012-2015 BEJ) - Suartini, Sri; Padikromo, Suparno (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
The study aims to conduct analysis themselves and provide empirical evidence that independent variable Managerial Ownership, ownership of Instisusional both partian or simultaneous effect on the value of the Corporation. This research uses the approach of kuantitative with a sample of 50 manufacturing companies registered in BEI during 2012-2015 with purposive sampling method. Then technical data analysis done with test statiistik using multiple regression. Research results showed variable Managerial Ownership and Institutional Ownership affect the value of the company. This finding is interesting that increased value of the company's success depends on the ability of the company to the maximum resources to empower and implement company policies that have been defined not by a factor of incentive Manager and supervision of instituonal.JEL Classification: G10, G17, G32Keywords: Institutional Ownership, Managerial Ownership, The Value of The Company